MEMBANGUN BUDAYA HUKUM INDONESIA DI ERA GLOBALISASI - Riski Febria Nurita Laga Sugiarto - (LPPM Universitas Putera Batam, 2018)
If today we are talking about a country called the Republic of Indonesia then we will not be much to talk about corruption, bribery, conflicts both internal conflict within the three highest institution in Indonesia as well as external conflict outside the institutions of the country, fighting between students as well as fighting between citizens in Indonesia itself, persecution, murder, rape and many others that we actually own has been embarrassed to talk about it because these things will not be there eventually. Especially if we are talking about the law in the era of globalization we are not going away talking about the law in Indonesia with the name of injustice,alignments, partiality, not autonomy and others. These things when we look back carefully, we will find something called